Comparative analysis of three approaches of antecedent part generation for an IT2 TSK FLS - Jaafar, Jafreezal (2017)
Since extreme learning machine is a non-iterative estimation procedure, it is faster than gradient-based algorithms which are iterative. Moreover, the extreme learning machine does not have any design parameters such as learning rate, covariance matrix, etc